2022
DOI: 10.1002/cbf.3741
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nitrate administration increases the expression the genes involved in the browning of white adipose tissue in female rats

Abstract: Nitrate, a nitric oxide (NO) donor, has antiobesity effect in female rats. This study hypothesized that the antiobesity effect of nitrate in female rats is due to the browning of white adipose tissue (WAT). Female Wistar rats (aged 8 months) were divided into two groups (n = 10/group): the control group received tap water and the nitrate group received water containing 100 mg/L of sodium nitrate for 9 months. At months 0, 3, 6, and 9, obesity indices were measured. At month 9, gonadal adipose tissue was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The BW-lowering effect of nitrate in current work was not linked to food intake, as food intake was unaffected by the nitrate intervention. It has been reported that nitrate is converted to nitrite and then to NO, decreasing BW by increasing cyclic guanosine monophosphate [ 42 ] and browning of white adipose tissue [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BW-lowering effect of nitrate in current work was not linked to food intake, as food intake was unaffected by the nitrate intervention. It has been reported that nitrate is converted to nitrite and then to NO, decreasing BW by increasing cyclic guanosine monophosphate [ 42 ] and browning of white adipose tissue [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, in addition to the increase in body weight, serum concentrations of progesterone and estradiol decreased, while those of LH and FSH increased at month 0 (2 months after ovariectomy and before nitrate intervention), confirming the successful establishment of the OVX model ( Yousefzadeh et al, 2020 ). The body weight-lowering effect of nitrate in OVX rats is attributed to its ability to mitigate OVX-induced adiposity ( Yousefzadeh et al, 2022c ), as evidenced by reduced adipocyte size and increased levels of brown adipose tissue ( Yousefzadeh et al, 2022c ; Yousefzadeh and Jeddi, 2022 ).…”
Section: Discussionmentioning
confidence: 99%